The inclusion of non-Western artistic traditions in cultural policy: Contrasting social justice and public diplomacy approaches. Issue 1 (1st April 2017) - Dupont, Pier-Luc
On both sides of the Atlantic, the dissemination of non-Western artistic traditions among the general public has been hampered by the prevalence of Eurocentric aesthetic standards in cultural institutions and organizations. In recent years, however, some states have taken steps in order to increase the exposure of immigrant-origin artists in a variety of disciplines, including theatre, music, dance, literature, cinema and visual arts. This article offers a systematic comparison of two such initiatives that have been developed at the national level: the Equity Office of the Canada Council for the Arts and Spain's network of cultural 'Houses' (Red de Casas). While the former was assigned a social justice mandate, the latter was created to further foreign policy goals through public diplomacy. These diverging approaches have created distinct funding opportunities, policy instruments and structural outcomes, with important implications for processes of artistic segregation and mainstreaming.